Byler-like familial cholestasis in an extended kindred. Issue 3 (September 1996) - Bourke, B; Goggin, N; Walsh, D; Kennedy, S; Setchell, K D; Drumm, B
Abstract : Progressive familial intrahepatic cholestasis (PFIC) occurs in many communities and races. A form of PFIC in five children from two consanguineous marriages in an Irish kindred is described. In addition, a review of clinical information from the records of three deceased members of the kindred strongly implies that they also suffered from PFIC. The children had a history of neonatal diarrhoea, sepsis, and intermittent jaundice that ultimately became permanent. They suffered intractable pruritus and growth retardation. Despite evidence of severe cholestasis, serum gamma-glutamyl transferase and cholesterol were normal in these children. Sweat sodium concentration were raised in three children. Liver histology showed severe intrahepatic cholestasis and hepatocellular injury. Urinary bile acid analysis revealed a non-specific pattern consistent with chronic cholestasis. These children suffer from a form of PFIC remarkably similar to that occurring in members of the Byler kindred.